Penguatan Ekonomi Umat Berbasis Pesantren Melalui OPOP dengan Pentahelix Model: (Studi Kasus pada Pesantren Tarbiyatut Tholabah dan Pesantren Sunan Drajat Lamongan) - Rif’ah, Sifwatir; Widyawati, Widuri; Aditya, Wahyu Faizal (Universitas Islam Lamongan, 2025)
Pesantren has a role as an agent of change for the people who are able to increase independence. The pesantren economic empowerment program is a flagship program of the government, especially the East Java Provincial Government through the One Pesantren One Product (OPOP) Program. The purpose of this study is to see the form of Entrepreneurship in PP Pesantren Tarbiyatut Tholabah and PP Sunan Drajat, as well as the role of OPOP in developing the economy of Islamic boarding schools using the pentahelix model approach. The research method is to use qualitative with a case study approach and the type is Field Research. And the data uses primary and secondary data through interviews, observations and library studies which are then analyzed descriptively. The results of this study indicate that the synergy of the pentahelix can produce several innovations that can help the economic independence of Islamic boarding schools such as the OPOP Mart Application, Grab OPOP Mart, OPOP Expo and Santri Digipreneur. This provides considerable benefits for the economic independence of Islamic boarding schools in East Java, especially in the Tarbiyatut Tholabah Islamic boarding school and the Sunan Drajat Islamic boarding school.